Efektivitas Penerapan Teknik Self Management Melalui Konseling Kelompok Untuk Mereduksi Prokrastinasi Akademik Siswa - Anisia Sarisafitri; Wens Nagul; Yohanes D. Doni (SOKO GURU: Jurnal Ilmu Pendidikan, 2024)
The effectiveness of applying self-management techniques through group counseling to reduce academic procrastination in students of class Xl IPS Sint Carolus Catholic High School for the 2023/2024 academic year?. The aim of this research is to determine the effectiveness of applying self-management techniques through group counseling to reduce academic procrastination in class XI IPS students at Sint Carolus Catholic High School for the 2023/2024 academic year.The method used in this research is quantitative descriptive with pre-experimental design (one group pretest-posttest design). The instruments used in this research were the academic procrastination questionnaire as a data collection instrument and intervention guidelines as a treatment instrument. The data analysis technique uses the t test formula. The results of the analysis show that the t_count value is 23.543, while the value at the 5% significance level is 2.776, so the . This shows that self-management techniques through group counseling are effective in reducing academic procrastination in class XI IPS students at Sint Carolus Catholic High School for the 2023/2024 academic year. Based on the results of this research, the researcher provides suggestions to: 1.) School principals are expected to increase cooperation with guidance and counseling teachers to facilitate group counseling activities through self-management techniques in reducing academic procrastination in students. 2.) Guidance and Counseling Teachers, to be able to provide group counseling services using self-management techniques to reduce academic procrastination in